Genetic Parameters and Divergence Studies for Gall Midge Incidence and Yield Components in Rice (Oryza sativa L.) - Chandra, B. Satish; Devi, K. Rukmini; Hari, Y.; Sridhar, V.; Prasad, K. Rajendra; Kumar, R. Shravan (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was carried out with 30 genotypes of rice (Oryza sativa L.) to study the variability and genetic divergence for yield contributing characters and gall midge incidence at Regional Agricultural Research Station, Warangal, Telangana during kharif, 2021 (July–November) in RBD replicated twice for eight quantitative traits. The phenotypic coefficient of variation (PCV) was slightly higher than the genotypic coefficient of variation (GCV) for all traits, indicating that environmental influences affect the expression of these traits. High heritability coupled with high genetic advance as % of the mean values were observed for 1000 grain weight and number of grains panicle-1 suggesting that selection for the improvement of these traits may be rewarding. The PCA analysis showed that first three principal components accounted for about 91.57%. Based on D2 studies, 30 genotypes were grouped into seven clusters with the cluster I (13) containing maximum number of genotypes followed by cluster III (9) and cluster II (4). Highest inter cluster distances were observed between the clusters IV and VII (1272.49) followed by IV and V (1097.39), VI and VII (1013.83) and II and VII (944.20) indicating the importance of the genotypes present in these clusters for exploiting heterosis for the desirable traits of these clusters. Days to 50% flowering (27.58%),1000-grain weight (27.36%) and plant height (27.36%) were found to be the most contributing traits towards total genetic diversity, which could be given due importance by the breeders for development of superior rice genotypes under crop improvement programme.